PELAKSANAAN FUNGSI DAN PROSES PEMBENTUKAN PERATURAN DAERAH DI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SUMATERA UTARA - Muhammad Yasser; Mirza Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Strengthening the function of forming regional regulations/legislative function of the DPRD in forming regional regulations has formal juridical legitimacy based on Article 18 paragraph (6) of the 1945 Constitution of the Republic of Indonesia that "Regional Governments have the right to establish regional regulations and other regulations to carry out autonomy and assistance duties .” As well as the enactment of Law Number 23 of 2014 concerning Regional Government and Law Number 17 of 2014 concerning the MPR, DPR, DPD and DPRD, it is hoped that the DPRD can be more active and productive in actualizing its function of forming regional regulations/legislative functions. However, unfortunately, so far the function of forming regional regulations in the DPRD of North Sumatra Province has been the object of research. The aim of this research is to find out and analyze the implementation of the legislative function of the DPRD of North Sumatra Province for the 2019-2024 period as well as knowing and analyzing the process of forming regional regulations in North Sumatra Province. This research uses a normative juridical method with an approach taken by examining all laws and regulations relating to the legal issues being handled. So, this research was carried out by analyzing theories related to the Implementation of the Regional Regulation Formation Function in the DPRD of North Sumatra Province in the Formation of Regional Regulations based on literature related to existing problems, and relevant laws and regulations. Keywords: Regional Regulations, Regional Autonomy, DPRD Functions Abstrak: Penguatan fungsi pembentukan peraturan daerah/fungsi legislasi DPRD dalam membentuk peraturan daerah telah mempunyai legitimasi secara yuridis formal didasari dalam Pasal 18 ayat (6) UUD NKRI Tahun 1945 bahwa “Pemerintahan Daerah berhak menetapkan peraturan daerah dan peraturan-peraturan lain untuk melaksanakan otonomi dan tugas pembantuan.” Serta berlakunya Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah dan Undang-Undang Nomor 17 Tahun 2014 tentang MPR, DPR, DPD dan DPRD mengharapkan DPRD dapat lebih aktif dan produktif dalam mengaktualisasikan fungsi pembentukan peraturan daerah/fungsi legislasi yang dimilikinya. Namun sayangnya, selama ini fungsi pembentukan peraturan daerah di DPRD Provinsi Sumatera Utara sebagai objek penelitian Tujuan penelitian ini adalah untuk mengetahui dan menganalisis pelaksanaan fungsi legislasi DPRD Provinsi Sumatera Utara Periode 2019-2024 serta mengetahui dan menganalisis proses pembentukan peraturan daerah Provinsi Sumatera Utara. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan yang dilakukan dengan menelaah semua undang-undang dan regulasi yang berkaitan dengan isu hukum yang ditangani. Maka, dalam penelitian ini dilakukan dengan menganalisis teori-teori yang berkaitan dengan Pelaksanaan Fungsi Pembentukan Peraturan Daerah di DPRD Provinsi Sumatera Utara dalam Pembentukan Peraturan daerah berdasarkan literatur-literatur yang berkaitan dengan permasalahan yang ada, dan peraturan perundang-undangan yang relevan. Kata kunci: Peraturan Daerah, Otonomi Daerah, Fungsi DPRD